Efficacy of Non-nuclear Methods Used for Hot Mix Asphalt Density Determination - Shah Zaman; Muhammad Hassaan; Jawad Hussain; Umar Hayat (Salehan Institute of Higher Education, 2020)
This paper presents research efforts with a major purpose of determining if electromagnetic, non-nuclear density gauges (NNDG) are competent enough for asphalt density measurement in comparison to the already existing standard core method (AASHTO T-166). Field, as well as laboratory studies, were conducted to assess the abilities of available non-nuclear devices as they need the appraisal for future use in many developing countries including Pakistan. NNDG data collected from 45 locations, compared to density determined in the laboratory for the cores extracted from the same location, shows that the results obtained from both the methods are comparable. Laboratory studies conducted on the slabs of open and dense gradations show that such an instrument performed well for dense gradation in comparison to open ones. The Calibration effect of the instrument has a valuable impact on the accurate density determination. Results indicated that such gauges are seriously affected by moisture presence on the surface of testing pavement. Moreover, the temperature dependency of non-nuclear gauges is among the major outcome of this research. Overall the performance of such gauges is valuable, and the results are comparable to the standard results of core methods. However, these results can only be used for Quality Assurance (Q.A) purposes and not for Quality Acceptance (Q.C) of the density of pavement.